Immune complex-induced haptokinesis in human non-classical monocytes - Preuß, Sophie L.; Oehrl, Stephanie; Zhang, Hao; Döbel, Thomas; Engel, Ulrike; Young, Jennifer L.; Spatz, Joachim P.; Schäkel, Knut (Frontiers in Immunology, 2023)
Formation and deposition of immune complexes (ICs) are hallmarks of various autoimmune diseases. Detection of ICs by IC receptors on leukocytes induces downstream signaling and shapes the local immune response. In many cases the pathological relevance of ICs is not well understood. We here show that ICs induce a distinct migratory response, i.e. haptokinesis in 6-sulfo LacNAc+ monocytes (slanMo) and in non-classical monocytes (ncMo) but not in intermediate (imMo) and classical monocytes (cMo). Using live imaging combined with automated cell tracking, we show that the main features of IC-dependent haptokinesis are elongation of the cell body, actin polarization at the leading edge, and highly directional migration. We find that CD16-dependent signaling mediates haptokinesis as blocking of CD16 or blocking SYK-signaling inhibited the migratory response. The activity of the metalloproteinase ADAM17 also modifies IC-dependent haptokinesis, likely at least partially via cleavage of CD16. Furthermore, using matrices with defined ligand spacing, we show that ligand density impacts the magnitude of the migratory response. Taken together, we have demonstrated that ICs induce a specific migratory response in ncMo but not in other monocyte subsets. Therefore, our work lays the groundwork for the investigation of IC-dependent haptokinesis in ncMo as a potential pathomechanism in IC-mediated autoimmune diseases.